Pattern of secretion of bioactive and immunoreactive gonadotrophins in normal pubertal children. - Dunger, D; Villa, A; Matthews, DR; Edge, J; Jones, J; Rothwell, C; Preece, M; Robertson, W (1991)
OBJECTIVE: The aim was to investigate the relationship between the nocturnal pulsatile secretory patterns of immunoreactive and bioactive luteinizing hormone in normal children at various stages of puberty. DESIGN: Blood samples were taken at 15-minute intervals from 2000 hours to 0800 hours. Pubertal stage was assessed by the method of Tanner (1962). PATIENTS: Thirty-four healthy siblings (17 males, 17 females) of diabetic children were recruited (median age 13.1, range 9.1-20.9 years). They were of normal height, non-obese, and covered the range of puberty. MEASUREMENTS: Follicle stimulating and luteinizing hormone levels were measured by radioimmunoassay in all 34 subjects; bioactive LH (B-LH) was assayed in a subgroup of 13 subjects selected to encompass the range of normal puberty. Oestradiol (girls) and testosterone (boys) were also measured at hourly intervals. RESULTS: Immunoreactive luteinizing and follicle stimulating hormone concentrations showed a progressive rise during puberty in both sexes. FSH concentrations were significantly higher in females than in males at all stages of puberty. Overnight mean bioactive luteinizing hormone concentrations were higher than immunoreactive luteinizing hormone levels in all the girls studied (n = 7). Although the number of bioactive luteinizing hormone pulses (31) was greater than immunoreactive pulses (27), the profiles were generally very similar. In the early pubertal girls an increase in the bioactive: immunoreactive ratio was observed during the middle of the night with the onset of pulsatility. Oestrogen was detected in the girls in breast stage 4-5 but not in two of the early pubertal girls, despite pulses of immunoreactive and bioactive luteinizing hormone. The boys had higher mean bioactive than immunoreactive luteinizing hormone levels and overall bioactive and immunoreactive luteinizing hormone and testosterone concentrations increased with puberty stage. Concordance between bioactive and immunoreactive hormone pulses was good although more immunoreactive pulses (16) were seen than bioactive pulses (14). As in the girls, an increase in the bioactive: immunoreactive ratio was observed in the middle of the night with the onset of pulsatility at genital stage 2 but, in contrast to the oestrogen data in the girls, testosterone secretion always followed luteinizing hormone pulsatility overnight. CONCLUSION: We conclude that mean overnight immunoreactive luteinizing and follicle stimulating hormone concentrations increase during puberty in both sexes. Bioactive luteinizing hormone levels are two to three times higher than immunoreactive luteinizing hormone in both sexes, but there is very little discordance between immunoreactive and bioactive luteinizing hormone pulsatility. The bioactive: immunoreactive ratio increases with the occurrence of pulsatility overnight in early pubertal children. The relationship between these changes in bioactive and immunoreactive luteinizing hormone and sex steroids is clearest in boys where the nocturnal testosterone rise always follows pulsatile LH secretion.